Plasmodium falciparum merozoite surface protein 6 (MSP-6) derived peptides bind erythrocytes and partially inhibit parasite invasion (2006)
This work shows that Plasmodium falciparum merozoite surface protein-6 (MSP-6) peptides specifically bind to membrane surface receptor on human erythrocytes. Three high activity binding peptides (HABPs) were found: peptides 31175 (41MYNNDKILSKNEVDTNIESN60) and 31178 (101YDIQATYQFPSTSGGNNVIP120) in the amino terminal region and 31191 (361EIDSTINNLVQEMIHLFSNNY380) at the carboxy terminal. Their binding to erythrocytes was saturable. HABPs 31191 and 31178 recognized 56 and 26 kDa receptors on erythrocyte membrane and inhibited in vitro Plasmodium falciparum merozoite invasion of erythrocytes by between 27% and 46% at 200 ?g ml?1 concentration, suggesting that these MSP-6 protein peptides play a possible role in the invasion process.